(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article talks about the history of the Great Silk Road, the history and place of large-scale cultural contacts and trade relations between the peoples of the East and West. In particular, issues such as the fact that this history is one of mutual cooperation, exchange and enrichment of cultures that form the basis of peace and development are highlighted.